Perceived Stigma and Treatment-Seeking Behavior in Individuals with Substance Use Disorder in Baghdad - Mohammed, Qahtan Q. (Journal of Contemporary Medical Sciences, 2016)
Objectives The present study aims at assessing the treatment-seeking behavior and perceived stigma among individuals with substance use disorder in Baghdad; identifying the impact of perceived stigma upon treatment-seeking behavior; and determining the relationship between perceived stigma and socio-demographic characteristics of substance abusers. Methods A descriptive, analytical study was established for the period from January to August, 2016. The study was conducted on a purposive sample of (50) substance abusers who are attending Substance Abuse Rehabilitation Centers at a teaching hospital in Baghdad. The instrument of the study is adopted and modified for the purpose of this study. Two scales were used in this study which is the Treatment Needs and Motivation Scale (TCU MOTForm), and Perceived Stigma of Substance Abuse Scale (PSAS). A self-administered report was applied as a mean of data collection. The data were analyzed through the application of descriptive and inferential statistical approaches which are applied by using IBM/SPSS Package version 20.0. Results The results of the present study showed that substance abusers were single (52%) with age ranged between 20–29 years old (54%), with barely sufficient monthly income (48%), and they do not work (40%). 72% of them were living in a high class neighborhood and they were substances abuser for more than two years duration (80%). The individuals with substance use disorder are showing a fair level of treatment-seeking behavior and they perceived moderate level of stigma. There is no significant impact of the stigma and sociodemographic upon the treatment-seeking behavior. And also, there is no significant relationship between perceived stigma and sociodemographic characteristics of individuals with substance use disorder. Conclusions The study concluded that perceived stigma among substance abusers has no impact upon their treatment-seeking behavior, and also, perceived stigma among substance abusers is insignificantly correlated with their socio-demographic variables.